2017
DOI: 10.1038/s41598-017-02209-x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of Opioid Analgesia for Chronic Pain: A Network Meta-Analysis

Abstract: Aim of this study was to study the tolerability of opioid analgesia by performing a network meta-analysis (NMA) of randomized-controlled trials (RCTs) which investigated effectiveness of opioids for the management of chronic pain. Research articles reporting outcomes of RCT/s comparing 2 or more opioid analgesics for the management of chronic pain were obtained by database search. Bayesian NMAs were performed to combine direct comparisons between treatments with that of indirect simulated evidence. Study endpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…9 A network meta-analysis comparing the adverse events between the opioids confirmed that tapentadol followed by oxycodone-naloxone combination was associated with least incidence of constipation. 10 Laxatives such as senna, lactulose, and co-danthramer were found to be useful in individual trials, but unfortunately small number of randomized controlled clinical trials with these agents precluded any firm conclusion in a Cochrane review. 11 Naloxone, alvimopan, naltrexone, naloxegol, and methyl naltrexone antagonize m receptor and form another group used for treating opioid-induced constipation.…”
Section: Introductionmentioning
confidence: 99%
“…9 A network meta-analysis comparing the adverse events between the opioids confirmed that tapentadol followed by oxycodone-naloxone combination was associated with least incidence of constipation. 10 Laxatives such as senna, lactulose, and co-danthramer were found to be useful in individual trials, but unfortunately small number of randomized controlled clinical trials with these agents precluded any firm conclusion in a Cochrane review. 11 Naloxone, alvimopan, naltrexone, naloxegol, and methyl naltrexone antagonize m receptor and form another group used for treating opioid-induced constipation.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies suggest that acute administration of tapentadol may not have significant advantages in gastrointestinal motor dysfunction, delaying gastric and small bowel transit, similarly to oxycodone (Jeong et al., ). In turn, a network meta‐analysis of randomized‐controlled trials showed tapentadol to have the best tolerability profile when compared to oxycodone‐naloxone, tramadol, oxycodone, fentanyl, morphine, hydromorphone, buprenorphine and oxymorphone, as it leads to the lowest rates of adverse events, constipation and trial withdrawal, ranking third for the ‘patient satisfaction’ criteria only (Meng et al., ). In a prospective open‐label study on tapentadol efficacy and tolerability in patients with moderate‐to‐severe cancer pain, pain intensity significantly decreased from baseline, with quality of life improvement and no changes in adverse effects; the tendency to increase the dose was low and independent of sex, age and pain mechanism (Mercadante et al., ).…”
Section: Clinical Applications and Efficacymentioning
confidence: 99%
“…Probably, the moderate affinity on MOR combined with the opioid-sparing effect due to NRI is responsible for the well-tolerable profile of TP 10. In chronic cancer and noncancer pain patients, Meng et al’s meta-analysis showed that the use of TP was associated with a better tolerability profile – lower withdrawal rate and adverse events (AEs)/constipation — when compared with other opioids 11. In a prospective study on opioid-naïve cancer patients, Mercadante et al12 demonstrated that TP was effective and well tolerated for treating moderate–severe chronic pain.…”
Section: Introductionmentioning
confidence: 99%